FORMULATION AND EVALUATION OF SUPERABSORBENT HYDROGEL FROM NATURAL POLYMER - BHELKAR, KRISHNAKANT B.; MOHARIR, KESHAV S.; KALE, VINITA V. (International Journal of Applied Pharmaceutics, 2023)
Objective: The objective of the present study was to synthesize the hydrogel from natural polymer and evaluation of its physical and chemical properties. Methods: Hydrogel was synthesized using graft co-polymerization technique from wheat starch, by crosslinking with acrylic acid. The product was purified, dried and micronized. It was then evaluated for water absorption and retention property at varying pH, FTIR, PXRD and Thermal analysis, microscopic, micromeritic and stability studies etc. Furthermore, the effect of NaOH treatment on prepared hydrogel material was studied. Results: Result of the studies revealed that superabsorbent hydrogel (SAH) product shows good water absorption capacity of 120g/g at neutral pH. Maximum water absorption capacity was at pH 9 which is 146.28g/g. Product shows good thermal stability, less cohesiveness and is amorphous in nature. In hygroscopicity study weight gain by SAH was 6.65% only while for unpurified SAH and NaOH treated SAH, it was 10.5% and 23.42% respectively. NaOH treatment shows a decrease in water absorption capacity by more than 40% also there is change in surface morphology of the product. Additionally, hygroscopicity was more and degradation rate was faster for NaOH treated hydrogel. Conclusion: Crosslinking with acrylic acid can form superabsorbent hydrogel material from the natural polymer such as wheat starch. The product shows excellent water absorption and retention capacity. pH affects water absorption capacity and shows maximum at pH 9 and at lower and higher pH it decreases to a significant level. There was decline in water absorption capacity and increase in hygroscopicity, when NaOH treatment is given to the SAH powder.